Rapid reactivation of aged NZVI/GO by Shewanella CN32 for efficient removal of tetrabromobisphenol A and associated reaction mechanisms. (20th January 2022) - Wang, Wenbing; Dong, Qianling; Qiu, Hao; Li, Hui; Mao, Yitao; Liu, Yiming; Gong, Tiantian; Xiang, Minghui; Huang, Yuan; Wang, Chen; Zan, Rixia
Abstract: Tetrabromobisphenol A (TBBPA) is one of the most widely applied brominated flame retardants, which has consequently resulted in severe environmental contamination. Graphene oxide-loaded nanoscale zero-valent iron (NZVI/GO) has previously shown excellent performance for potential TBBPA removal. However, the aging of NZVI/GO resulted in reduced reaction rates. In this study, Shewanella CN32 was used to reactivate the performance of aged NZVI/GO. The results demonstrated that CN32 significantly reactivated aged NZVI/GO (27%) and consequently improved the removal of TBBPA by 240% in aged NZVI/GO+CN32 (92%). Compared to aged NZVI (0.07 mM), CN32 rapidly decomposed the iron oxide passivation layer of aged NZVI/GO, with a subsequent increase in the release of Fe 2+ ions (0.12 mM). Moreover, Fe(II) vivianite (Fe II 3 (PO4 )2 ·8H2 O) and SO4 2− type green rust (Fe3.6 Fe0.9 (O, OH, SO4 )9 ) formed at the surface of aged NZVI/GO+CN32. GO accelerated the reduction of dissimilatory iron ( α -Fe2 O3 ) and the formation of vivianite crystals. Vivianite further improved the debromination of TBBPA. Furthermore, the semiquinone radicals (C=O) in the interface of the aged NZVI/GO effectively mediated electron transfer and reactivated the performance of aged NZVI/GO by CN32. It could therefore be concluded that CN32-induced iron oxide reduction and NZVI exposure, C=O mediated electron transfer, and vivianite-induced debromination were the main removal mechanisms of TBBPA in the system. It is a potential technology for convenient remediation of soil, groundwater, and lake. Graphical abstract: Image 1 Highlights: The aged NZVI/GO was significantly reactivated by CN32 and the system released more Fe 2+ . Upon increasing the sodium lactate to 20 mM, the reaction rate kobs of TBBPA was increased by 174%. Increasing the aged NZVI/GO provided more C=O and mediated faster e − transfer to increase kobs . Vivianite and SO4 2− type green rust formed during the biological reduction of aged NZVI/GO by CN32. GO accelerated dissimilatory iron reduction and structural Fe(II) vivianite crystal formation.